Effect of promethazine on seizure activity and its interactions with antiepileptic drugs diazepam and phenytoin in Rats - Warudkar, Sandesh; Shinde, Vinod; Borkar, Archana (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Current antiepileptic drugs (AEDs) are effective in controlling seizures in about 70% patients but use is often limited by adverse effects. Promethazine, H1 receptor antagonist, has a controversial status in patients of epilepsy. Both pro and antiepileptic effect has been documented in various animal studies. Hence, this study was designed to see the effect of promethazine, an H1 antihistaminic drug and its interactions with antiepileptic drugs in rats. Methods: The effect of promethazine (10mg/kg) and its interactions with antiepileptic drugs diazepam and phenytoin was assessed by using maximal electroshock seizures (MES) and chemoshock (PTZ) method. Results: Promethazine along with diazepam in subtherapeutic doses exerted significant protection against MES induced seizures whereas no such protection was observed with PTZ method rather the seizure threshold was reduced. Conclusions: Subtherapeutic doses of Promethazine alone and in combination with diazepam showed protection against seizures in MES method. However, proconvulsant effect was seen with PTZ method suggesting histamine plays a protective role in development of seizures. This shows dual behavior of promethazine on MES and PTZ induced seizures.